2017
DOI: 10.1123/jpah.2016-0415
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Elastic Resistance Exercise on Muscle Strength and Functional Performance in Healthy Adults: A Systematic Review and Meta-Analysis

Abstract: ERE are effective to improve functional performance and muscle strength when compared with no intervention, in healthy adults. ERE are not superior to other methods of resistance training to improve functional performance and muscle strength in health adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 0 publications
6
33
0
Order By: Relevance
“…To help people and facilitate exercise execution, we suggested elastic resistance training (ERT) for some exercises. Its benefits include improved functional capacity, increased strength and endurance and represent safe equipment during homeconfinement (20). Exercises should be repeated from 8 to 12 times per session.…”
Section: A Potential New Way To Promote An Active Lifestylementioning
confidence: 99%
“…To help people and facilitate exercise execution, we suggested elastic resistance training (ERT) for some exercises. Its benefits include improved functional capacity, increased strength and endurance and represent safe equipment during homeconfinement (20). Exercises should be repeated from 8 to 12 times per session.…”
Section: A Potential New Way To Promote An Active Lifestylementioning
confidence: 99%
“…A recent systematic review found that training with elastic bands improved muscle strength in “healthy” and “not healthy” older adults, with more pronounced effects in healthy participants [ 59 ]. Elastic resistance exercise also improves functional performance and muscle strength in adults in comparison with no exercise, and is equally effective in improving muscle strength, but not function as traditional resistance training [ 60 ]. Training with elastic bands and tubes can also improve body composition in overweight older [ 61 ] and postmenopausal women [ 62 ], and cardiometabolic markers such as C-reactive protein, glycosylated hemoglobin in patients with the metabolic syndrome [ 63 ].…”
Section: Pump It Up No Iron Neededmentioning
confidence: 99%
“…Shahar et al conducted a study with sarcopenic elderly and showed that soy protein did not provide additional effect on RT responses. However, both studies have used RT with elastic band, which can produce different responses from RT with machines . Moreover, training status can influence OS responses to RT and whey protein together.…”
Section: Introductionmentioning
confidence: 99%
“…However, both studies have used RT with elastic band, which can produce different responses from RT with machines. 17 Moreover, training status can influence OS responses to RT and whey protein together. In young adults, the training status did not influence OS responses to RT alone 18 ; however, these results cannot be extrapolated to older people taking protein supplementation.…”
Section: Introductionmentioning
confidence: 99%